2008
DOI: 10.1007/s00186-008-0272-3
|View full text |Cite
|
Sign up to set email alerts
|

A fluid model for a relay node in an ad hoc network: the case of heavy-tailed input

Abstract: Relay nodes in an ad hoc network can be modelled as fluid queues, in which the available service capacity is shared by the input and output. In this paper such a relay node is considered; jobs arrive according to a Poisson process and bring along a random amount of work. The total transmission capacity is fairly shared, meaning that, when n jobs are present, each job transmits traffic into the queue at rate 1/(n + 1) while the queue is drained at the same rate of 1/(n + 1). Where previous studies mainly concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…This idea has been used in several papers before, see e.g. [24,44], or, in a more complex model, [7]. The proof consists of a lower bound that focuses on the probability of the single most likely event, in conjunction with an upper bound that shows that all other scenarios (for instance those with multiple big jumps) yield negligible contributions.…”
Section: Heavy-tailed Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea has been used in several papers before, see e.g. [24,44], or, in a more complex model, [7]. The proof consists of a lower bound that focuses on the probability of the single most likely event, in conjunction with an upper bound that shows that all other scenarios (for instance those with multiple big jumps) yield negligible contributions.…”
Section: Heavy-tailed Inputmentioning
confidence: 99%
“…The proof consists of a lower bound that identifies a most likely scenario, and an upper bound that shows that all other scenarios lead to asymptotically negligible contributions; the line of reasoning resembles that of earlier papers, e.g. [7,44].…”
Section: Introductionmentioning
confidence: 96%
“…The focus of [20] was on the validation of the fluid model for m ≥ 1; by system simulations incorporating all details of the  802.11e ireless  technology (see, e.g., [11]) it was demonstrated that the fluid model accurately captures the resource sharing amongst source nodes and a common relay node. In [2] the fluid model for m = 1 is analyzed in the special case of regularly varying (that is, heavy-tailed) flows. The tail asymptotics of the overall flow transfer time are derived by sample-path arguments; it is proven that the tail behaves roughly as the residual flow size.…”
Section: Literaturementioning
confidence: 99%
“…Fluid queues has became a fascinating area of research, in recent years due to its wide spread applicability in computer and communication systems [1,3], manufacturing systems [6] etc. A stochastic fluid flow model is an input-output system where the input is modelled as a continuous fluid that enters and leaves the storage devices called a buffer according to randomly varying rates.…”
Section: Introductionmentioning
confidence: 99%